The Representation of Nyai Ontosoroh's Character in "Bumi Manusia" within Contemporary Ethnic Fashion Design - Yuni Diantari, Ni Kadek; Udiyana Wasista, I Putu; Ari Darmastuti, Putu (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2025)
This study represents literary characters in contemporary ethnic fashion design, emphasizing the character of Nyai Ontosoroh from Pramoedya Ananta Toer's novel Bumi Manusia. Nyai Ontosoroh was chosen to represent a strong, intelligent indigenous woman who resists colonialism and patriarchy. The purpose of this research is to interpret Nyai's character values into visual clothing forms through a descriptive qualitative approach with textual narrative analysis. Values such as assertiveness, independence, and courage are translated into clothing design silhouettes, the selection of sekar jagad batik motifs, and symbolic color combinations. The influence of 19th-century European fashion is implemented through the distinctive silhouette of the kebaya kutubaru, reflecting Nyai's character as a traditional woman with progressive ideas. This research also applies the principles of narrative fashion, which uses clothing as a medium for conveying stories and cultural values. This paper reveals that clothing design can serve as an effective visual medium for expressing literary narratives and cultural identity. The representation of Nyai Ontosoroh's character through design not only produces aesthetic works but also expands reflective, contextual design practices rooted in local values. This research contributes to the development of an interdisciplinary approach between fashion, literature, and cultural studies in Indonesia's creative sector.